Historical and cultural development of Iranian Kheymeh Shab Bazi from Qajar dynasty to present / Saba Aslian - Saba , Aslian (2014)
Kheymeh Shab Bazi is the name of Iranian marionette puppet theatre that goes back to at least 800 years ago. It is usually performed in a small booth at night. “Historical and cultural development of Kheymeh Shab Bazi from Qajar dynasty to the present” is a qualitative historical research according to Cultural Memory Theory. This corrent research is conducted to investigate development procedure in Iranian marionette puppet theatre in three aspects; application, elements and structure of performance. A historical and cultural review of Kheymeh shab bazi before Qajar dynasty is also presented. Changes in elements including puppets and puppetry, actor (Morshed), story and music band are studied from Qajar dynasty to the present. Valuable historical evidences are reported and studied to find out the structure of performance during Qajar period. Also, a list of puppets and puppetry instruments and Iranian musical instruments that are used in Kheymeh Shab Bazi are reported to introduce all parts of Kheymeh Shab Bazi. This research shows connections between Kheymeh Shab Bazi and Iranian culture from the past to the present.